Engineering of hole-selective contact for high-performance perovskite solar cell featuring silver back-electrode - Lin, Liujin; Gu, Chenjie; Zhu, Juye; Ye, Qiufeng; Jiang, Ershuai; Wang, Wei; Liao, Mingdun; Yang, Zhenhai; Zeng, Yuheng; Sheng, Jiang; Guo, Wei; Yan, Baojie; et al. (Journal of materials science, 2019)
Replacement of commonly gold (Au) with other non-precious metals is a crucial step for low-cost perovskite solar cells (PSCs). However, severe performance degradations always occurred when we get rid of the Au electrode, mainly because of the deteriorated hole-transporting properties. Here, we reported that the efficiency of the PSCs featuring silver (Ag) back-electrode can be increased from 17.02 to 18.62% after introducing a thin molybdenum trioxide (MoO 3 ) film in between the Spiro-OMeTAD and the Ag electrode. Characterizations from impedance spectrum and dark current density showed that the addition of MoO 3 can effectively reduce the series resistance and reverse saturation current density of the devices, thereby leading to improved fill factor and open-circuit voltage. The enhancements in hole transport and extraction at the interface were further confirmed by the external quantum efficiency and photoluminescence tests. Our results suggested that silver electrode with MoO 3 is a promising design strategy for efficient and cost-effective PSCs.